Peran istri nelayan dalam meningkatkan pendapatan keluarga di Desa Mowundo Kecamatan Molawe Kabupaten Konawe Utara - Ramadani, Puspa; Sarinah; Rosmawati; Yusuf, Sarini; Patiung, Seventry Meliana (Jurnal Sosial Ekonomi Perikanan, 2022)
The purpose of this research was to examine the amount of revenue, profit and business feasibility which obtained by the business people of lobster cultivation. This research was conducted from January to February 2020 in Soropia Subdistrict, Konawe Regency, Southeast Sulawesi. The population in this study were lobster cultivators who used Floating Net Cages (KJA) was one person and Fence Net Cages (KJT) consisted of 3 people. The sample was determined using the census technique. The data were obtained through interviews using questionnaires, observation, documentation and literature studies. The data analysis which used was quantitative analysis using the formula of revenue, profit and feasibility analysis. The results of the analysis showed that lobster cultivation with KJT, the revenue which obtained was (Rp 49,893,333/cycle), Profit (Rp 35,638,635/cycle), R/C Ratio (3,49), NPV (Rp 1,619,345/cycle) and Internal rate of return (IRR) (26%). Meanwhile, the lobster cultivation with KJA, the revenue which obtained was (Rp 63.600.000/cycle), Profit (Rp 37,237,453/cycle), R/C Ratio (2,41), NPV (Rp 9,364,761/cycle) and IRR (43 %). The conclusion of this research was that the lobster cultivation with KJT and KJA system was profitable and feasible to be developed.